2017
DOI: 10.1186/s13550-017-0264-5
|View full text |Cite|
|
Sign up to set email alerts
|

3D skeletal uptake of 18F sodium fluoride in PET/CT images is associated with overall survival in patients with prostate cancer

Abstract: BackgroundSodium fluoride (NaF) positron emission tomography combined with computer tomography (PET/CT) has shown to be more sensitive than the whole-body bone scan in the detection of skeletal uptake due to metastases in prostate cancer. We aimed to calculate a 3D index for NaF PET/CT and investigate its correlation to the bone scan index (BSI) and overall survival (OS) in a group of patients with prostate cancer.MethodsNaF PET/CT and bone scans were studied in 48 patients with prostate cancer. Automated segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…In the last few years, convolutional neural networks (CNNs) have revolutionized the field of image analysis, and they are now the first option for image classification, detection and segmentation. CNNs have already been trained to accurately segment organs in CT (Lindgren Belal et al ., ; Roth et al ., ). However, due to misalignment between the PET and CT modalities, a direct transfer of a CT‐based prostate segmentation to the PET image often leads to voxels in the bladder being incorrectly classified as prostate.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…In the last few years, convolutional neural networks (CNNs) have revolutionized the field of image analysis, and they are now the first option for image classification, detection and segmentation. CNNs have already been trained to accurately segment organs in CT (Lindgren Belal et al ., ; Roth et al ., ). However, due to misalignment between the PET and CT modalities, a direct transfer of a CT‐based prostate segmentation to the PET image often leads to voxels in the bladder being incorrectly classified as prostate.…”
Section: Methodsmentioning
confidence: 95%
“…The proposed method requires approximate knowledge of the position of the prostate in CT. This is achieved by first running a simple segmentation network on the CT image (Lindgren Belal et al ., ; Roth et al ., ). Figure shows the overall structure of our CNN.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…The optimal SUV threshold values for application of 18 F‐NaF PET/CT have not been standardized and should be determined based on the underlying pathologic condition and the goals of the evaluation. In several oncologic studies of patients with prostate cancer, researchers used an SUV threshold > 15 for 18 F‐NaF uptake to segment bone metastases . In other oncologic studies utilizing 18 F‐NaF PET/CT scans to evaluate metastatic diseases from a variety of cancer types, an SUV threshold of > 10 was applied .…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of total skeletal metastatic burden is possible with 18F‐fluoride PET as there is generally high contrast between metastases and normal bone. In prostate cancer, a number of studies have shown that global quantitative metrics can predict treatment response and progression‐free survival or overall survival …”
Section: Pet and Pet/ctmentioning
confidence: 99%